Selected Examples of the Longest Deadjectival Suffix Chains and Their Attestation in Pleteršnik’s Dictionary - Stramljič Breznik, Irena (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
The paper analyses the longest deadjectival four- and five-suffix chains extracted from the Word-Family Dictionary of Slovene for headwords beginning with b, and examines their attestation in synchronic lexicographic sources and in Pleteršnik’s Dictionary. Quantitative data confirm the structural constraints of Slovene word formation: with the increasing derivational stage, the number of realised deriv-atives decreases considerably, which makes the longest chains rare and often limited to isolated lexicalised items. A comparative analysis of contemporary lexicographic sources and Pleteršnik’s Dictionary shows that Pleteršnik predom-inantly records lower-stage members of derivational chains, whereas complete chains are only rarely attested. This may reflect both the lexicographic concept of the dictionary and diachronic changes in the lexicon and in the productivity of individual word-formation patterns.